Knowledge integration in the Quran: A case of its economic content - Tazul Islam; Mohd Zohdi Mohd Amin; Syed Ahmad Tarmizi Syed Omar; Adnan Mohamed Yusoff; Zamrie Ibrahim @ Musa; Robiatul Adawiyah Mohd @ Amat; Khairul Anuar Mohamad; Norazman Alias; Kauthar Abd Kadir; Abdul Rahman Hussein Obeid; Abdullaah Jalil; Mohammed Akhiruddin Ibrahim; et al. (American Scientific Publishers, 2024)
Indexed by Scopus/ERA